Hubungan Status Gizi Dengan Gangguan Siklus Menstruasi Pada Remaja Putri SMAN 13 Makassar - Irmawati S.; Riska Sari; Musfira Aziz (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Nutritional status affects the menstrual cycle. If a woman with a nutritional status is thin, fat tissue which is also a source of low estrogen will produce low estrogen, causing disruption to the menstrual cycle by looking at the relationship between nutritional status and menstrual cycle disorders in young women at Sman 13 Makassar. This research uses an observational analytical research design with a cross-sectional approach. Purposive sampling was used to determine the sample size. The data analysis technique uses the chi square test and ordinal regression